A Study on the Status and Contributory Factors of Adverse Events Due to Negligence in Nursing Care. Issue 8 (December 2021) - Kim, Min Ji; Jang, Seung Gyeong; Kim, In Sook; Lee, Won
Abstract : Background: Patient safety issues in medical institutions have received worldwide attention. Nurses play a pivotal role in providing health care at the bedside and the interception of adverse events (AEs). A knowledge of contributory factors for these AEs is vital to individuals, institutional procedures, and also national policy. The goals of this study are to analyze medical litigation related to nursing practice and to determine the most common contributory factors of AEs due to negligence in nursing care. Methods: A qualitative content analysis was conducted for AEs related to nursing care to determine the general characteristics and contributory factors. The contributory factors for each case were examined using a modified version of the Yorkshire Contributory Factors Framework. Results: The most common types of AEs in nursing involved surgeries, procedures/interventions, and medications. The analysis also revealed that situational factors and communication and culture factors contributed most to AEs. Individual staff factors and staff training and education were the most frequent subfactors contributing to AEs. Conclusions: Adverse events were associated with various contributory factors that varied according to AE type. Thus, strategies need to be developed based on the understanding of these contributory factors related to the different AE types so that comprehensive approaches to improving patient safety and quality of nursing care can be implemented.